SETTLEMENT OF LAND DISPUTE RIGHTS ULAYAT PEOPLES KAJANG WITH PT. PP LONDON SUMATERA INDONESIA IN BULUKUMBA DISTRICT - Mahmud Mahmud (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
This research aims to Can provide solutions to problems arising or encountered in the problem of agrarian law in particular regarding the resolution of land disputes in PT. PP London Sumatera Indonesia in Bulukumba District. The type of research used in this writing is empirical research or normative empirical, i.e. an approach that refers to the written rules or other legal materials that are secondary to see how the implementation/implementation through a field research conducted with sociology and interviews, so that the information obtained clarity about the investigation. The writing of this thesis also uses historical research as a complement to field data. Research on the author's history use in terms of the study of the indigenous Kajang tribe and the beginning of the entry PT. PP London Sumatera Indonesia in Bulukumba District. The result showed that Settlement of land dispute rights Ulayat people of Kajang tribe with PT. PP London Sumatera Indonesia has been pursued through litigation (judicial process) and non-litigation (alternate) lines. Dispute resolution through litigation is not able to properly and comprehensively describe disputes. This can be seen from the ruling of the Supreme Court Decree No. 2553/K/PDT/1987 dated 31 July 1990 which could not be executed properly in the execution caused by The legal factor itself (MA verdict) is a multi-interpretation, law enforcement factor (judge) in deciding the previous thing does not do field verification (object dispute), factors of facilities, infrastructure in terms of unclear boundaries and the factors of society that lack understanding the law of formal and cultural factors are not accommodated in the decision of the court.